The meaning of the oral tradition Penganjak Kuda Sitajur in the accompaniment of kulcapi within the Karo community - Sinulingga, Ramanta; Purba, Mauly; Ginting, Pulumun Peterus (International Journal of Culture and Art Studies, 2026)
The study examines the oral tradition of "Penganjak Kuda Sitajur," prevalent in the Karo community, focusing on the semiotics of narrative and the role of the kulcapi, a musical instrument, as a supporting medium in storytelling. This tradition reflects the cultural, social, and religious values of the Karo community through the heroic tales of the Sitajur character, narrated musically. Using a qualitative approach with ethnographic methods, the research relies on primary data from interviews, observations, and field documentation. The semiotic theories of Jacques Derrida and Roland Barthes are employed to decode denotative, connotative, and mythical meanings conveyed in this tradition. Meanwhile, Derrida’s theory will reveal a deeper meaning, or what is known as the theory of deconstruction, regarding the story of the Sitajur horse. The findings reveal that "Penganjak Kuda Sitajur" is not merely an oral narrative but a cultural expression imbued with values of character education and local wisdom. The kulcapi plays a vital role in enhancing emotional depth and narrative structure, making this tradition unique among oral traditions. The study highlights that despite changes in form and medium, the essence and moral messages of the tradition remain preserved and continuously revitalized by the Karo society.